Minimal Interference from Possessor Phrases in the Production of Subject-Verb Agreement - Nicol, Janet L.; Barss, Andrew; Barker, Jason E. (Frontiers in Psychology, 2016)
We explore the language production process by eliciting subject-verb agreement errors. Participants were asked to create complete sentences from sentence beginnings such as The elf's/elves' house with the tiny window/windows and The statue in the elf's/elves' gardens. These are subject noun phrases containing a head noun and controller of agreement (statue) and two nonheads, a “local noun” (window(s)/garden(s)), and a possessor noun (elf's/elves'). Past research has shown that a plural nonhead noun (an “attractor”) within a subject noun phrase triggers the production of verb agreement errors, and further, that the nearer the attractor to the head noun, the greater the interference. This effect can be interpreted in terms of relative hierarchical distance from the head noun, or via a processing window account, which claims that during production, there is a window in which the head and modifying material may be co-active, and an attractor must be active at the same time as the head to give rise to errors. Using possessors attached at different heights within the same window, we are able to empirically distinguish these accounts. Possessors also allow us to explore two additional issues. First, case marking of local nouns has been shown to reduce agreement errors in languages with “rich” inflectional systems, and we explore whether English speakers attend to case. Secondly, formal syntactic analyses differ regarding the structural position of the possessive marker, and we distinguish them empirically with the relative magnitude of errors produced by possessors and local nouns. Our results show that, across the board, plural possessors are significantly less disruptive to the agreement process than plural local nouns. Proximity to the head noun matters: a possessor directly modifying the head noun induce a significant number of errors, but a possessor within a modifying prepositional phrase did not, though the local noun did. These findings suggest that proximity to a head noun is independent of a “processing window” effect. They also support a noun phrase-internal, case-like analysis of the structural position of the possessive ending and show that even speakers of inflectionally impoverished languages like English are sensitive to morphophonological case-like marking.